Securing the iRODS Metadata Catalog for Digital Preservation - Antunes, G. J. (2009)
Digital preservation is the ability to retrieve, access, and use digital objects through time, while ensuring the authenticity and integrity properties of these objects. Data grids represent a model of storage systems designed for data management and sharing, which concept also has been proposed for digital preservation. However, since data grids are not specifically designed for this purpose, they present weaknesses that have to be handled. This poster will present a set of services to address a problem in the metadata catalog of the iRODS data grid, strengthening that platform for digital preservation purposes.